Atraumatic Sport-Related Medial Sesamoid Pain: Conservative Treatment Outcome and Magnetic Resonance Imaging Features - Choi, Jun Young; Choo, Suk Kyu; Song, Tae Hun; Suh, Jin Soo (Clinics in orthopedic surgery, 2024)
This study aimed to evaluate the effectiveness of conservative treatment in selected patients with atraumatic medial sesamoid pain (MSP) that developed during sports activities. The secondary aim was to determine the detailed underlying pathology in patients who did not respond to conservative treatment using magnetic resonance imaging (MRI). From March 2015 to August 2022, we prospectively followed 27 patients who presented to our outpatient clinic with atraumatic sports-related MSP. The conservative treatment protocol for MSP included the use of oral analgesics, activity restriction, insole modification, local corticosteroid injections, and boot walker application with crutches. MRI was performed for all patients who experienced persistent pain despite the completion of conservative treatment. After the completion of the conservative treatment protocol, 48.1% of the patients reported a reduction in pain. Patients with younger age at pain onset ( = 0.001), higher body mass index ( = 0.001), and a bipartite medial sesamoid ( = 0.010) were more likely to experience persistent pain after conservative treatment. The type of sports activity was also a factor since running- and dancing-related MSP tended to respond better to conservative treatment compared to MSP originating from golf, futsal, and weightlifting with squatting. On MRI, 42.8% of patients showed no specific abnormal findings, with signal changes in soft tissues such as the subcutaneous fat and bursa being the most common, followed by intraosseous signal changes of the medial sesamoid bone and chondral or subchondral lesions of the medial sesamoid metatarsal joint (28.6% each). Conservative treatment was successful in less than half of the patients who experienced MSP due to sports activity. Practitioners should be aware of the numerous possible causes of conservative treatment failure, such as bursitis, medial sesamoiditis, stress fracture, or chondral lesions between the medial sesamoid and metatarsal. MRI evaluation may be helpful in MSP patients who do not respond to conservative treatment.